1999
DOI: 10.1177/154193129904301802
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Differences in Stress Responses during Simulated Driving

Abstract: A study of group differences in susceptibility to stress during simulated driving is reported. 74 drivers participated, with approximately equal numbers of younger (18-25) and older (55-78) drivers, and of men and women. Stress was manipulated by exposing half the sample to a failure experience; frequent, uncontrollable skids. Following the stress manipulation, drivers' hazard perception, speed and vehicle control were assessed. Subjective state before and after the drive was assessed by questionnaire. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…Results showed that: (i) age negatively affects all driving measures considered in this study; (ii) measures of overall cognitive functioning significantly predicted traffic stress resilience and the ability to manage an overview of the traffic visual scene; (iii) measures of object-based spatial mental transformation significantly predicted the performance in both stress resilience and visual reaction task; (iv) significant effects of self-based spatial skills were found on stress resilience and, in interaction with the gender, on visual acquisition; and (v) the interaction between cognitive and demographic predictors mitigated in a non-significant way the effects of these predictors only on measures of stress resilience and speed reaction but not on measures of motor speed and visual acquisition. The background research approaching individual differences in driving performance demonstrated that aging affects driving skills due to decline in sensory, cognitive, and motor functioning (e.g., Matthews et al, 1999;Mathias and Lucas, 2009;Fraade-Blanar et al, 2018;Kunishige et al, 2019;Ledger et al, 2019a). The current study supports previous findings in which gender differences were related to differences in stress vulnerability (Matthews et al, 1999) and in reaction times (Matthews et al, 1999;Der and Deary, 2006;Dykiert et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Results showed that: (i) age negatively affects all driving measures considered in this study; (ii) measures of overall cognitive functioning significantly predicted traffic stress resilience and the ability to manage an overview of the traffic visual scene; (iii) measures of object-based spatial mental transformation significantly predicted the performance in both stress resilience and visual reaction task; (iv) significant effects of self-based spatial skills were found on stress resilience and, in interaction with the gender, on visual acquisition; and (v) the interaction between cognitive and demographic predictors mitigated in a non-significant way the effects of these predictors only on measures of stress resilience and speed reaction but not on measures of motor speed and visual acquisition. The background research approaching individual differences in driving performance demonstrated that aging affects driving skills due to decline in sensory, cognitive, and motor functioning (e.g., Matthews et al, 1999;Mathias and Lucas, 2009;Fraade-Blanar et al, 2018;Kunishige et al, 2019;Ledger et al, 2019a). The current study supports previous findings in which gender differences were related to differences in stress vulnerability (Matthews et al, 1999) and in reaction times (Matthews et al, 1999;Der and Deary, 2006;Dykiert et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…The background research approaching individual differences in driving performance demonstrated that aging affects driving skills due to decline in sensory, cognitive, and motor functioning (e.g., Matthews et al, 1999 ; Mathias and Lucas, 2009 ; Fraade-Blanar et al, 2018 ; Kunishige et al, 2019 ; Ledger et al, 2019a ). The current study supports previous findings in which gender differences were related to differences in stress vulnerability ( Matthews et al, 1999 ) and in reaction times ( Matthews et al, 1999 ; Der and Deary, 2006 ; Dykiert et al, 2012 ). Regarding education, previous research showed that level of education was not related to vehicle-crash involvement when compared to other variables, such as annual mileage ( Lourens et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was found regardless of general control beliefs or controllability condition, perhaps because the driving domain coupled with divided attention involving cognitive tests is particularly stressful for older adults (Matthews et al, 1999). Interestingly, younger participants did not show a cortisol response to the driving challenge, on average, as shown in Figure 2, perhaps because they have more experience with video/driving games or find driving and divided attention to cognitive tasks less stressful than older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of age on performance were stronger than those of either gender or stress. (Matthews, 1999(Matthews, , 1009.…”
Section: Identify Research and Collect Ideamentioning
confidence: 99%